Root nitrogen transformation and mineral composition in selected forage legumes - Nnadi, L.A.; Haque, I. (Cambridge University Press, 1988)
Presents results of a study conducted at Debre Zeit, Ethiopia, to examine the differences in mineral composition, root N contents and their rates of transformation in the soil of different species of four genera of forage legumes, viz, Trifolium, Lablab, Medicago and Vicia. Also examines the effect of P application on the biomass production and mineral composition on the tops and roots of these legumes.